The CaT stretcher: An open-source system for delivering uniaxial strain to cells and tissues (CaT) - Wang, Yushi; Singer, Ryan; Liu, Xinyue; Inman, Seth J.; Cao, Quynh; Zhou, Quan; Noble, Alex; Li, Laura; Arizpe Tafoya, Aidee Verónica; Babi, Mouhanad; Ask, Kjetil; Kolb, Martin R.; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
Integration of mechanical cues in conventional 2D or 3D cell culture platforms is an important consideration for in vivo and ex vivo models of lung health and disease. Available commercial and published custom-made devices are frequently limited in breadth of applications, scalability, and customization. Herein we present a technical report on an open-source, cell and tissue (CaT) stretcher, with modularity for different in vitro and ex vivo systems, that includes the following features: i) programmability for modeling different breathing patterns, ii) scalability to support low to high-throughput experimentation, and iii) modularity for submerged cell culture, organ-on-chips, hydrogels, and live tissues. The strategy for connecting the experimental cell or tissue samples to the stretching device were designed to ensure that traditional biomedical outcome measurements including, but not limited to microscopy, soluble mediator measurement, and gene and protein expression remained possible. Lastly, to increase the uptake of the device within the community, the system was built with economically feasible and available components. To accommodate diverse in vitro and ex vivo model systems we developed a variety of chips made of compliant polydimethylsiloxane (PDMS) and optimized coating strategies to increase cell adherence and viability during stretch. The CaT stretcher was validated for studying mechanotransduction pathways in lung cells and tissues, with an increase in alpha smooth muscle actin protein following stretch for 24h observed in independent submerged monolayer, 3D hydrogel, and live lung tissue experiments. We anticipate that the open-source CaT stretcher design will increase accessibility to studies of the dynamic lung microenvironment through direct implementation by other research groups or custom iterations on our designs.